PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI PADA GURU SMA N 18 TEBO - Trisnawati, Winda; Lestari, Renda; Habibah, Nur; Oktavia, Diana; Balti, Levandra; Kurniawan, Ridho; Ellbas, Cenby Rosella Agustin (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
Training on the learning media - based technology for teachers at SMA N 18 Tebo which aims to improve the ability of teachers to develop learning media -based technology in the form of learning videos. This training implementation method is carried out using a team-based project method, teachers work on projects in the form of interactive and interesting learning videos. The learning video is then uploaded to the YouTube channel. YouTube is one of the social media platforms that are often used by children today. This is considered effective as well as changing the mindset of students that the use of the internet and social media also helps in the learning process and becomes fun. In practice, the service team will conduct training for 4 weeks, in order to provide tutorials and evaluations to teachers at SMA N 18 Tebo.